The influence of visual supports and motivation on motor performance of the MABC-2 for Chinese school-aged children with autism spectrum disorder - Xiaoyi Hu (Nature Portfolio, 2021)
Abstract The influences of including visual supports and strategies to increase motivation for children with autism spectrum disorder (ASD) in motor assessments were examined. 97 children with ASD and 117 age-matched typically developing (TD) children performed the Movement Assessment Battery for Children, Second Edition (MABC-2) under traditional, visual support, motivation, and visual support plus motivation protocols. Results showed that children with ASD elicited lower MABC-2 scores than TD children. Moreover, in children with ASD, the visual support protocol, but not the motivation protocol, produced higher scores on ball and balance skills than the traditional protocol. These findings indicated that children with ASD were developmentally delayed in motor skills; however, their performance may be improved by including visual supports in motor assessments.